A retrospective descriptive cross-sectional study of Oral Dosage Form Administered in The Form of Suspension to ICU Patients at Hospital X - Nelly Suryani; Vidia Arliani Anwar; Yardi Saibi; Estu Mahanani Dhilasari; Sabrina Dahlizar; Ofa Suzanti Betha; Ismiarni Komala; Afifah Nurnishrina Azzahra (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2024)
Patients in the intensive care unit were often very sick and had lost consciousness. Because they had trouble swallowing, individuals with reduced awareness frequently depended on enteral tubes (NGT) for their daily medical and nutritional requirements. Since not all medications were accessible in parenteral forms, patients who relied on enteral tubes often had issues, including drug stability. Many problems arose in clinical usage when the medication was crushed or suspended and put into the NGT, including drug obstruction in the enteral tube and a reduction in drug stability as a result of the dose form being altered, making the drug unstable. Thus, this study aimed to ascertain the stability of oral suspension medications given to intensive care unit patients. The medical records of intensive care unit patients who had received oral medication therapy at X Hospital in Jakarta were examined retrospectively using a cross-sectional, descriptive approach. According to the statistics, coated tablets accounted for 68% of the most frequently used oral medication preparations. It was highly likely that crushing the coated tablets and administering them via NGT had resulted in tube obstruction. Additionally, 59.26% of the medications used had exhibited hygroscopic qualities, and several had been readily hydrolyzed. Based on these findings, it was concluded that oral medications, particularly crushed-coated tablets, could negatively affect drug stability. Active substances with hygroscopic properties and those prone to hydrolysis were also identified as potential contributors to instability.